Simulating seasonal variability of phytoplankton in stream water using the modified SWAT model. (December 2019) - Pyo, JongCheol; Pachepsky, Yakov A.; Kim, Minjeong; Baek, Sang-Soo; Lee, Hyuk; Cha, YoonKyung; Park, Yongeun; Cho, Kyung Hwa
Abstract: The ability to simulate algal systems is critical for watershed-scale models. The objective of this study was to develop and evaluate a modified algal module that simulates the dynamics of three major algal groups (cyanobacteria, green algae, and diatoms) in a stream using variables available in the Soil and Water Assessment Tool. The proposed module 1) models the dynamics of the three algal groups while accounting for nutrients from algal die-off and 2) has temperature multipliers that consider the effect of temperature changes on kinetic rates. Data to test the module were collected from a forest-dominated watershed over two years. The modified module was efficient in predicting seasonal variations in algal group biomass and simulated the regeneration of nutrients after algal die-off. This module will be useful in predicting the dynamics of the three studied algal groups and evaluating the best management practices for algal blooms in watersheds. Highlights: The modified algal module was applied to the SWAT model. The algae-specific temperature correction term was applied to the process rates. The regeneration of organic nutrients after algal die-off was reasonably introduced. The module successfully reproduced the seasonal variation in phytoplankton biomass.